Estimation of Proper Implant Length in the Posterior Region of the Maxilla by using Digital and Conventional Panoramic Radiographs "Comparative Study" (Mustansiria Dental Journal, 2018)
This Study was done to compare between the digital and conventional panoramicradiography in the estimation of the distance between the crest of alveolar bone to thefloor of maxillary sinus for proper dental implant in the posterior region of maxilla.Twenty patients were selected, they need multiple implants in different posterioredentulous regions of the maxilla, in the period from (January 2006-April 2006), 11were males and 9 females of age between (37-52). All the patients were sending fordigital and conventional panoramic radiographic examination. Comparison was donefor the two types of radiographs with tracing chart readings of Friadent system for themeasurement of implant length.The study shows that obvious differences between the digital and conventionalpanoramic radiography in comparison to tracing chart, while no differences weredetected between the digital panoramic radiographs and the tracing chart.The study reported that the digital panoramic radiography is more accurate inestimation of proper bone measurement than conventional radiographs for precisedental implant selection.